Effect of Concept Mapping on Student’s Achievement in Inorganic Chemistry - Ghimire, Paras Mani (Ganeshman Darpan, 2022)
The globalized world with historically diverse inheritance has carried with it ‘not so good’ side of gender discrimination. Women continue to be ‘unequal half’ of men due to the psychological barrier of patriarchally-structured society that has covertly institutionalized male supremacy and male hegemony. Through the journey of women empowerment, the world has been struggling to offer a gender-free life. This article attempts to analyze the status of women empowerment and highlights the related issues and challenges. This study is a content analysis of literature from secondary source. It reveals that women are relatively disempowered and continue to hold the ‘subordinated statuses compared to men in spite of loud propaganda of the efforts undertaken to achieve gender equality in real life. The article suggests holistic ways to rethink context-driven women empowerment and concludes that changes in social norms and beliefs, access to life-skill education, and equal participation in decision making are the major enabling factors for this.